Differences and Similarities Between Eastern and Western Rhinoplasty: Features and Proposed Algorithms. Issue 2 (March 2021) - Lao, William Wei-Kai; Hsieh, Tung-Ying; Ramirez, Alejandro E.
Abstract : Abstract: The authors collectively reviewed their experiences in performing rhinoplasty in North America, Asia, and South America and categorized common undesirable features in Eastern and Western rhinoplasty and their respective surgical algorithms. In Western rhinoplasty, the surgery is often reduction in nature. The proposed algorithm is a dorsum-first, tip-second surgical sequence to better suit the need of this population. Meanwhile in Eastern rhinoplasty, the surgery is often augmentation in nature with extra materials needed to build the nose. The proposed algorithm is the opposite, a tip-first and dorsum-second surgical sequence.